Modeling of Transport Process of Biological Fluids in the Material with Two-Level Porosity; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Nazarenko N. N. (2015, 2015)
Title screen